Rwanda Petroleum Exploration Capacity Building Project - World Bank (Washington, DC, 2013)
The petroleum sector is not very well developed at the present time in Rwanda. The only petroleum related activity at this time in Rwanda is the extraction of dissolved methane from the waters of Lake Kivu. This report is the result of a short term consulting contract with the World Bank Group and FJG energy advisors concluded on September 1st 2009. This report is a result of a mission to Rwanda September 12th-25th, 2009. It is not intended as an in depth analysis of the capacity needs for the petroleum sector in Rwanda, as this was completed in March 2009 by bridge consult AS, but rather as an evaluation of the 'practical and operational' perspectives in developing a local petroleum industry focused on exploration. Further advice in dealing with potential interested companies was also offered in the context of an overarching petroleum policy. The main objectives of the assignment were to: enhance the familiarity on the part of key government officials with the main technical and economic concepts of the petroleum exploration and production industry; develop understanding within Government of Rwanda of the potential impacts (positive and negative) of an active petroleum exploration and production industry in a developing country; familiarize government officials with the fundamental policy issues they will face as petroleum exploration and development activities unfold in Rwanda with an emphasis on those up-front policy decisions needed at the earliest phases of activity; and prepare key officials to take a front line role in policy formulation and negotiation with private investors.